Understanding Management Roles and Organisational Behaviours in Planning and Scheduling Based on Construction Projects in Oman - Nasseri , Hammad Al; Aulin, Radhlinah (Penerbit Universiti Sains Malaysia, 2016)
There are many challenges associated with the construction processes of planning and scheduling. These challenges are relevant to all project parties or stakeholders and therefore management roles or organisational behaviours of those parties have to be properly considered and assessed. With this in mind, this study is aimed at assessing practitioners' perspectives on the current significance and applicability of a set of criteria or factors concerned with management roles and organisational behaviours of the different parties based on construction projects in Oman. The study has adopted a quantitative approach in which a questionnaire-based survey was chosen and conducted to gather responses from construction projects in Oman. A total of 67 valid responses were analysed based on the rankings and means of the respondents' perspectives on the significance and applicability of the identified factors to current practice. The overall findings indicated that all investigated factors should be critically considered as equally important to the development process of planning and scheduling. Nevertheless, the findings implied that a management priority should be given to the most important factors significantly affecting project planning and scheduling. The study provides some useful recommendations on how to improve project management roles and organisational behaviours in planning and scheduling on the part of key project parties.